Association between graft function and serum TNF-α, TNFR1 and TNFR2 levels in patients with kidney transplantation. (24th February 2015) - Budak, Deniz; Yilmaz, Vural Taner; Akbas, Halide; Suleymanlar, Gultekin; Yucel, Gultekin
Abstract: Introduction : This prospective observational study aimed to assess the relevance of serial postoperative serum TNF-α, TNFR1 and TNFR2 measurements for predicting graft function and acute rejection episodes (AR) after transplantation. Materials and methods : We studied 50 kidney transplant recipients (31 female, 19 male; mean age: 38.36 ± 12.88). Blood samples were collected immediately before and after surgery at day 7, month 1 and month 3. Serum TNF-α, TNFR1 and TNFR2 levels were measured by ELISA using a commercial kit (Invitrogen ELISA). Serum cystatin-C levels were measured by particle-enhanced immunonephelometric method. Glomerular filtration rate (GFR) was estimated by Chronic Kidney Disease-Epidemiology (CKD-EPI) equation. Patients were assigned to their transplant outcomes in terms of acute rejection [AR(+) and AR(−)] and slow (SGF) or immediate graft function (IGF). Results : Among 50 recipients, six had AR(+) and 44 had AR(−), depending on graft function: 17 had SGF and 33 had IGF. Serum creatinine, cystatin-C, TNF-α, TNFR1 and TNFR2 levels demonstrated consistent significantly decreases after transplantation while GFR values had consistent increases ( p = 0.001). Pretransplant levels were not statistically different between AR(+) and AR(−) groups (TNF-α: 30.79 ± 5.96 vs. 27.95 ± 2.43 pg/mL, TNFR1: 55.96 ± 21.6 vs. 40.52 ± 7.41 ng/mL, TNFR2: 58.31 ± 8.06 vs. 50.9 ± 3.34 ng/mL, respectively) ( p > 0.05). Serum TNF-α, TNFR1 and TNFR2 levels on day 7 and month 1 were also significantly higher in AR(+) group compared to AR(−) ( p = 0.012, p = 0.049 for TNF-α, p = 0.001, p = 0.002 for TNFR1, p = 0.001, p = 0.002 for TNFR2). Conclusions : Our preliminary findings suggest that serum TNF-α, TNFR1 and TNFR2 levels might be considered useful markers of evaluating graft function after renal transplantation.